Bijeenkomst in Amicitia tegen 3,5 % loonsverlaging en voor kortere werktijden en meer banen - Singels, Han,
Bijeenkomst in Amicitia tegen 3,5 % loonsverlaging en voor kortere werktijden en meer banen.